Road identification for its‐integrated systems of automotive active safety - Ivanov, Valentin; Shyrokau, Barys; Siakhovich, Vladzimir (Transport, 2005)
The paper discusses several aspects of active safety control for automotive application. Particular emphasis is placed on the fuzzy logic determination of friction properties of a tyre‐road contact. An example of vehicle control systems equipped with off‐board sensors of road roughness, temperature, moisture and rain intensity demonstrates the implementation of this approach. The paper proposes conceptual solutions for preventive active safety control applied to vehicles which are integrated in an intelligent transportation system.First Published Online: 27 Oct 2010